Trooping to the supermarket exploring behaviors of 3-4 year olds in a public setting (Compendium of Human Ecology Researches in the Philippines, 2003)
Twenty one children ages 3-4 years old enrolled at the Day Care Laboratory of UPLB were taken to a community field trip in an attempt to observe acceptable behaviors in a public place last January 19, 2012. The kids in class were made to pretend that were made to pretend that they were picking items from grocery shelves and queuing up at the cashier. Seventeen out of the 21 children were reported to be excited, anticipating and unusually bubbly or talkative before the trip. Three were observed to have no change in behavior and one child was found to be unusually difficult on the day of the trip. Although nine of the children were wandering politely request to buy a familiar